Descriptive Writing Skills Utilizing A Fishbone Method: A Practical Approach Towards English Students - Munawir, Ahmad (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The objectives of this research are to discover the extent to which (1) the use of fishbone can influence the students’ descriptive writing skills and (2) to see which of the five aspects of writing is enhanced the most when utilizing fishbone. A quasi-experimental approach was used in this study. The study took place at Public Senior High School, Gowa, South Sulawesi, Indonesia. The sample size for the study was 62 students, whereas the experimental and control classes had 31 students, respectively. The data was obtained using a written test as a pre-test and post-test for both classes, and the test results were analyzed using the SPSS 24.0 program. The results revealed that two components of writing were improved by the application of the fishbone method, namely content, and organization, while the other components were not improved. It refers to the probability value (0.052) being greater than or equal to the significance level (= 0.05). While, the variant score of the five writing components showed that the probability value (0.00) was lower than the significant value (0.05), the mean score of the five writing components indicated that organization was higher than others. That leads to the conclusion that (1) the application of the fishbone method did not improve the students’ descriptive writing skills and (2) the highest improvement of the five writing components was organization.